Alveolar bone remodeling during maxillary incisor intrusion and retraction - Seok Yoon Hong (Progress in Orthodontics, 2019)
Abstract Background Maxillary incisor protrusion is a prevalent dental deformity and is often treated by upper incisor intrusion and retraction. The mechanical loading triggers the resorption and apposition of the bone. Alveolar bone remodeling is expected to follow orthodontic tooth movement in a one-to-one relationship. However, in many cases, the outcomes are different. Alveolar bone might still remain thick causing lip protrusion and other aesthetic problems after treatment. Additional corrective procedures such as alveoloplasty. On the other hand, if the labial bone becomes too thin, periodontal problems like gingival recession might occur. The unpredictability of the treatment result and the risk of requiring corrective procedures pose significant challenges to both the providers and patients. The aim of this study is to determine factors that can help to predict the alveolar bone reaction before maxillary incisor intrusion and retraction. Methods The cohort included 34 female patients (mean age 25.8 years) who were diagnosed with skeletal class II malocclusion with upper incisor protrusion. These patients underwent extraction and orthodontic treatment with upper incisor intrusion and retraction. Lateral cephalograms at pre-treatment and post-treatment were taken. Linear and angular measurements were analyzed to evaluate the alveolar bone changes based on initial conditions. Results The study found that the relative change, calculated as change in alveolar bone thickness after treatment divided by the initial alveolar thickness, was inversely correlated with the initial thickness. There was a significant increase of labial alveolar bone thickness at 9-mm apical from cementoenamel junction (B3) (P < 0.05) but no statistically significant change in the thickness at other levels. In addition, the change in angulation between the incisor and alveolar bone was inversely correlated with several initial angulations: between the initial palatal plane and upper incisor angle, between the initial palatal plane and upper incisor labial surface angle, and between the initial palatal plane and bone labial surface angle. On the other hand, the change in labial bone thickness was neither significantly correlated with the initial thickness nor significantly correlated to the amount of retraction. Conclusion The unpredictability of alveolar bone remodeling after upper incisor intrusion and retraction poses significant challenges to treatment planning and patient experience. The study showed that the initial angulation between the incisor and alveolar bone is correlated with the change in angulation after treatment, the initial thickness of the alveolar bone was correlated with the relative change of the alveolar bone thickness (defined as change in thickness after treatment divided by its initial thickness), and the amount of intrusion was correlated with the alveolar bone thickness change at 9-mm apical from the cementoenamel junction after treatment. The results of the present study also revealed that the change in labial alveolar bone thickness was neither significantly correlated with the initial thickness nor significantly correlated to the amount of retraction.